Radioactivity analysis of soil samples taken from the western and northern shores of Lake Van, Turkey - Kayakoku, Halime; Dogru, Mahmut (Pergamon-Elsevier Science Ltd, 2017)
In this study, concentrations of the radioactive isotopes Ra-226, Th-232, K-43 and Cs-137 were measured in soil samples from the shores of Lake Van using a high purity germanium detector. Activity concentrations obtained for these nuclides were compared with world average values. The average Ra-226, Th-232 and K-40 activity concentrations calculated for the soil samples were higher than the world average values reported by UNSCEAR. The lowest Ra-226, Th-232 and K-40 activity concentrations were recorded in sample T-1 whereas the highest values were recorded in sample T-11. Concentrations of C-137 in the samples ranged between 0.91 +/- 0.01 and 29.68 +/- 0.33 Bq kg(-1). In order to evaluate the radiological hazards resulting from natural radioactivity, radium equivalent activities, absorbed dose rates, and internal and external hazard indices were calculated and the results were compared with internationally recognized values.
Keywords: Natural radioactivity; Radionuclide; Radium equivalent; Lake Van